ECONOMIC IMPACT OF E-COMMERCE ON MACROECONOMICS: A REVIEW ON GLOBAL PERSPECTIVE (International Journal of Food and Nutritional Sciences, 2022)
E-commerce technology has significantly altered the way that businesses operate and consumers shop, causing a shift from traditional to online shopping that directly affects both consumers and producers. This essay offers a thorough analysis of the macroeconomic effects of e-commerce technology, looking at how it affects important metrics like GDP, employment, trade, and productivity. We examine the potential advantages and difficulties of e-commerce for various stakeholders, including policymakers, businesses, and consumers, using data from a variety of sources. According to the current analysis, e-commerce technology has a significant potential to boost economic growth, boost productivity, and generate new job opportunities. It also brings up some significant difficulties, such as worries about job displacement, privacy and security concerns, and potential detrimental effects on conventional brick-and-mortar businesses. As a result, there is a need for more research to understand the precise factors that influence how e-commerce affects the economies of various regions and nations, as well as its long-term effects on conventional retail businesses and wider societal effects. To better understand how government policies can promote the expansion of e-commerce and guarantee that traditional businesses operate on an even playing field, more research is required. Finally, we stress the importance of further investigation to the potential environmental effects of online shopping and its carbon footprint. Overall, this paper sheds light on the potential advantages and drawbacks of e-commerce technology and emphasizes the significance of decision-makers, companies, and customers in navigating this globally changing landscape.